Heart rate and heart rate variability response to the transpiration of vortex-water by Begonia Eliator plants to the air in an office during visual display terminal work [corrected] [published erratum appears in J ALTERN COMPLEMENT MED 2008 Nov;14(9):1175]. - Johansson B (Journal of Alternative & Complementary Medicine, 2008)
OBJECTIVES: This study explores the effects of vortex-water transpired from indoor greenery to office air, in relation to heart rate and heart rate variability during exposure to an electromagnetic field (EMF) from a visual display terminal (VDT). DESIGN: The study followed a randomized prospective single group cross-over design. SUBJECTS: Fifty (50) healthy volunteers, seated in any ordinary working posture in front of a VDT. INTERVENTION: Electrocardiography was measured in five 10-minute sequential tests. The VDT was turned off during the first test and switched on for the subsequent four tests. During tests 3 and 4, one of two Begonia Eliator plants, irrigated with either tap water or vortex-rotated (active) tap water during growth, was placed adjacent to the VDT. Heart rate, heart rate variability (HRV) and power spectral density (PSD) were analyzed. RESULTS: The heart rate was unchanged at the start of EMF exposure. The time domain measurements indicated a significant decrease in heart rate and a significant increase in HRV, accompanied by higher vagal tone in the presence, and finally in the absence, of the active plant. PSD parameters revealed significantly higher total power, as well as an increase in low frequencies (LF) and high frequencies (HF) in the condition induced by the active plant as well as after its removal. Very low frequencies (VLF) increased at EMF exposure whereas normally HF power decreased, accompanied by a rise in LF power and LF/HF ratio. HF power was higher at exposure to the active compared to the control plant. Spectral power density diagrams revealed an intensified spectral power band at frequencies of around 0.1 Hz at the condition of both plants, indicating systemic autonomic stability. CONCLUSIONS: The findings suggest that the parasympathetic response was associated with reduced heart rate, implicating restoration and maintenance of metabolic energy resources mediated by an involuntary adaptation to active plant-related stimuli.